2021
DOI: 10.1177/0033354921999407
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Methodologic and Practical Considerations for Life Expectancy as a Public Health Mortality Measure

Abstract: Introduction Life expectancy is a public health metric used to assess mortality. We describe life expectancy calculations for US counties and present methodologic considerations compared with years of potential life lost before age 75 (YPLL-75) and premature age-adjusted mortality (PAAM), 2 commonly used length-of-life metrics. Methods We used death data from the National Center for Health Statistics for 2015-2017 and other health measures from the 2019 County Health Rankings & Roadmaps. We calculated life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In Germany, like in many other high-income countries (e.g., [31][32][33][34][35][36]), life expectancy at birth differs markedly among different parts of the country, i.e., among federal states, regions and districts [1,2,8,37,38]. A recent study on district-level life expectancy in Germany [2] demonstrated that average life expectancy at birth varied among Germany's 401 districts by 5.3 years for men and 3.9 years for women, based on the period life tables of 2015/17.…”
Section: Introductionmentioning
confidence: 99%
“…In Germany, like in many other high-income countries (e.g., [31][32][33][34][35][36]), life expectancy at birth differs markedly among different parts of the country, i.e., among federal states, regions and districts [1,2,8,37,38]. A recent study on district-level life expectancy in Germany [2] demonstrated that average life expectancy at birth varied among Germany's 401 districts by 5.3 years for men and 3.9 years for women, based on the period life tables of 2015/17.…”
Section: Introductionmentioning
confidence: 99%
“…Global-scale evidence indicates that environmental, not genetic, explanations are strongly implicated in populationlevel health disparities. For example, life expectancy is a common public health measure (Roubal et al, 2021), and despite a fairly constant genetic background, it shifts dramatically based on environment (The World Bank, 2019a; The World Bank, 2019b). For example, immigrants to the United States from nations with lower life expectancies than the United States experience increased life expectancy beyond the average US-born individual, though their US-born descendants do not (Argeseanu Cunningham et al, 2008;Mehta et al, 2016;Bastian et al, 2020).…”
Section: Environment and Genetics Interact To Produce Healthmentioning
confidence: 99%